Spice bioactives in edible packaging - Ravi, K.; Goyal, K.; Priyadarshi, S.; Naidu, M. M (Journal of Spices and Aromatic Crops, 2020)
Edible packaging received significant attention in recent years. The main advantage of edible packaging over synthetic packaging is that they are environment friendly. The material used in edible packaging (lipids, polysaccharides, proteins) is generally recognized as safe and it acts as a barrier to gases, light and moisture. Spices have been traditionally used for its medicinal value. Spice extract or its essential oil possesses various bioactive compounds which are known for their antioxidant and antimicrobial property. Incorporation of spice extract or its essential oil into edible packaging exerts antimicrobial activity against the food pathogens thus preventing food spoilage and enhances the shelf-life and also increases the nutritional value of the final product. Antioxidant properties of spices retard the lipid oxidation. Dietary allergy and intolerance are also associated with packaging material and spices. Because of the high cost of film-forming material, scaling-up of edible packaging has remained a problem.